Alexithymia and Suicide Risk in Psychiatric Disorders: A Mini-Review - De Berardis, Domenico; Fornaro, Michele; Orsolini, Laura; Valchera, Alessandro; Carano, Alessandro; Vellante, Federica; Perna, Giampaolo; Serafini, Gianluca; Gonda, Xenia; Pompili, Maurizio; Martinotti, Giovanni; Di Giannantonio, Massimo (Frontiers in Psychiatry, 2017)
It is well known that alexithymic individuals may show significantly higher levels of anxiety, depression, and psychological suffering than non-alexithymics. There is an increasing evidence that alexithymia may be considered a risk factor for suicide, even simply increasing the risk of development of depressive symptoms or per se. Therefore, the purpose of this narrative mini-review was to elucidate a possible relationship between alexithymia and suicide risk. The majority of reviewed studies pointed out a relationship between alexithymia and an increased suicide risk. In several studies, this relationship was mediated by depressive symptoms. In conclusion, the importance of alexithymia screening in everyday clinical practice and the evaluation of clinical correlates of alexithymic traits should be integral parts of all disease management programs and, especially, of suicide prevention plans and interventions. However, limitations of studies are discussed and must be considered.